Serum Irisin Levels Are Positively Correlated with Physical Activity Capacity in Hemodialysis Patients - Zhengjia Fan; Feng Wu; Peixin Wang; Leiyun Wu; Jialing Zhang; Wen Li; Qi Pang; Aihua Zhang (Kidney & Blood Pressure Research)
Introduction: Regular physical activity is beneficial for health but is often reduced in patients receiving maintenance hemodialysis treatment. Irisin is a muscle-secreted hormone that reportedly improves metabolism and slows down the progression of some chronic diseases. In this study, we aimed to investigate the relationship between physical activity capacity and serum irisin levels in hemodialysis patients. Methods: Our study included 252 patients undergoing hemodialysis at Xuanwu Hospital Capital Medical University. Enzyme-linked immunosorbent assay was used to measure blood irisin levels. Body composition was analyzed by bioelectrical impedance analysis. The International Physical Activity Questionnaire (IPAQ) was used to score physical activity ability. Results: Bivariate correlation analysis showed a positive correlation between IPAQ scores and ln irisin (the natural logarithm of irisin; r = 0.326, p < 0.001). Independent determinants of IPAQ scores were ln irisin, age, fasting glucose, and carbon dioxide combining power. Conclusion: Our findings provide the first clinical evidence that serum irisin levels are positively correlated with physical activity capacity in hemodialysis patients.